ANALISIS PENERIMAAN SISWA TERHADAP PENGGUNAAN APLIKASI UJIAN ONLINE BERBASIS KOMPUTER MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL - Afifah Nabila Atiqoh; Adlia Alfiriani; Rini Novita (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
The study aims to determine student acceptance of the Computer Based Test application at SMK Negeri 1 Sitiung. The type of research used is quantitative with the type of survey research. The method used in this research is the Technology Acceptance Model (TAM) method. The data analysis technique used is descriptive analysis and prerequisite test analysis. Based on the partial research results, the perceived ease of use (PEOU) variable obtained from the tcount value of 3.706> 1.677 with a significant value of 0.001 <0.05 means that H0 is rejected Ha is accepted. The perceived usefulness variable (PU) obtained from the tcount value of 1.841 < 1.677 with a significant value of 0.072> 0.05 means that H0 is accepted Ha is rejected. The attitude towards use (ATU) variable obtained from the tcount value of 6.244> 1.677 with a significant value of 0.001 <0.05 means that H0 is rejected Ha is accepted. Based on simultaneous research, the tcount value is 68,100> 2.80 and the sig value. 0.001 <0.05 this means H0 is rejected Ha is accepted. As for the effect of learning outcomes after using the application, previously students were less active in using the internet or computers since the use of the Computer Based Test application for the learning outcomes themselves, students are more active, especially playing an active role in using the internet.